THE USE OF TWO FREQUENCY VARIABLES IN THE DISTRIBUTED CIRCUITS SYNTHESIS. - Balanyuk , Yurii (Science-based technologies, 2024)
One of the approaches to the design of filters from segments of non-uniform lines is the use of NLs connected by a quadrupole between the generator and the load. In this case, the required characteristic of selectivity is achieved by changing the wave resistance of the line according to a certain law. However, the input op of the NL loaded with an active resistance cannot be purely reactive at real frequencies, so the reflection coefficient cannot be equal to unity at any of them. Therefore, it is fundamentally impossible to obtain a significant attenuation at least at one point outside the passband of the filter. Only by choosing a certain class of complex loads can significant attenuation be achieved outside the passband. Another principle of filter construction is based on the use of the simplest heterogeneous lines that perform the functions of resonators. The necessary selective characteristic of the filter is achieved by selecting the parameters of resonators and communication circuits. This method of building filters is more rational. In addition, in the process of synthesis, you can use ideas and techniques characteristic of circles from segments of uniform lines. It is shown that in the synthesis of distributed circuits based on transmission lines, complex functions of two frequency variables should be used, which allows the construction arbitrary circuit functions and fully cover the classes of physically realized transfer functions. A description of the elements "inductance" and "capacitance" in the class of functions of two complex frequency variables was obtained, which allows synthesizing circuits using the ideas and methods of Richards’s circuit theory.